2017
DOI: 10.19082/4806
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and character of abdominal hernia in Arar City, Northern Saudi Arabia in 2017

Abstract: BackgroundAbdominal wall hernias are a very common surgical condition affecting all ages and both sexes. The main risk factors of hernias include pregnancy, weight lifting, constipation, and weight gain.ObjectiveThe aim of this study was to determine the prevalence and risk factors of abdominal hernias, their causes, treatment and complications among both sexes of the Arar population (Saudi Arabia).MethodsA cross-sectional study was conducted among 1,567 adults living in Arar city in 2017. Data was collected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 10 publications
6
49
2
4
Order By: Relevance
“…Inguinal hernia is the most common hernia among abdominal wall hernias [ 1 , 2 ]. Inguinal hernia can range from being asymptomatic to painful especially with coughing, exercise, or bowel movement [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inguinal hernia is the most common hernia among abdominal wall hernias [ 1 , 2 ]. Inguinal hernia can range from being asymptomatic to painful especially with coughing, exercise, or bowel movement [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The patient can feel the bulge by touching the affected area or notice it when standing upright. It may be possible to push a hernia back into the abdomen, however, this is only possible according to the type of the hernia and the size of the hernia sac content [6] . In the present study, we aim at evaluating the awareness of the predisposing factors of hernia among adults in Riyadh city in KSA.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study done by Ahmed Alenazi A et al also showed that, hernias were significantly more prevalent in females than in males (63.4% vs. 36.6%) [12].…”
Section: Discussionmentioning
confidence: 87%